Design of the Monopulse Feeding Network for a Slotted Waveguide Array on an Annular Disk - Zongxin Wang; Yulan Wang; Shengchi Zhu; Peng Chen (International Journal of Antennas and Propagation)
Design of a monopulse feeding network including a compact power distribution network and a monopulse comparator for a dual polarization slotted waveguide array fabricated on an annular disk is presented in this paper. As the slotted waveguide array is arranged on an annular disk, the feeding network is more complicated than that of a regular array such as a rectangular array. The design details of some key waveguide components, such as the compact assembly of H-plane T-junctions and E-plane elbows used to connect power distribution networks and radiation waveguides, are provided. Quasiplanar magic tees are designed and used to construct the compact sum and difference comparator. The antenna system contains two comparators, which are used to generate sum and difference beams for horizontal polarization and vertical polarization, respectively. Finally, the monopulse slotted waveguide array antenna is divided into two modules, a comparator module and an antenna module (including power distribution network), and fabricated with the layered processing and bonding process. The comparator module is measured using a network analyzer to verify its amplitude-frequency characteristics and phase-frequency characteristics. Screwing the comparator module and the antenna module together, a monopulse slotted waveguide array antenna is obtained, and the sum beam and difference beam characteristics of the antenna are measured in a microwave chamber and presented.